Gambaran Covid-19 terhadap stres ibu post partum - Fara Millinia Suwares; Rilyani Rilyani; Linawati Novikasari (JOURNAL OF Mental Health Concerns, 2023)
Background: Based on data from the Bandar Lampung City Health Office in 2020, the three major coverage of post partum mothers at the Bandar Lampung City Health Center were the highest at Puskesmas Panjang 14.29%, Puskesmas Kedaton 11.83%, Puskesmas Sukaraja 10.92% (Health Department Bandar Lampung City, 2020). Preliminary data conducted at the Kedaton Health Center by looking at the number of pregnant women in November amounted to 54 postpartum mothers, and preliminary data conducted at the Sukaraja Health Center by looking at the number of pregnant women in November 2021 as many as 80 postpartum mothers. Purpose: To know the description of the Covid-19 on post partum maternal stress in the Bandar Lampung City Health Center Work Area in 2022. Method: This type of research is quantitative, descriptive research method, population and sample are post partum mothers at Sukaraja Health Center and Kedaton Public Health Center Bandar Lampung City, the sampling technique uses purposive sampling. Data analysis using univariate by presenting the percentage of data. Results: The number of post partum mothers in Sukaraja Health Center and Kedaton Health Center were 50 respondents (100%). Respondents who were not exposed to Covid-19 partum at the Sukaraja Health Center and Kedaton Health Center were 50 respondents (100%). The description of post partum maternal stress at the Sukaraja Health Center with normal categories 5 respondents (10.0%), mild stress 11 respondents (22.0%), moderate stress 22 respondents (44.0%), and severe stress by 12 respondents (24 ,0%). While at the Kedaton Public Health Center with normal categories 11 respondents (22.0%), mild stress 14 respondents (28.0%), moderate stress 15 respondents (30.0%), and severe stress by 10 respondents (20.0%). Conclusion: The picture of postpartum maternal stress at Sukarja and Kedaton Community Health Centers is both at a moderate stress level, with a percentage of 44% for Sukarja Community Health Center and 30% for Kedaton Community Health Center. Suggestion: Health workers are expected to increase their efforts to provide good counseling to individuals and families, especially pregnant women and post partum  Keywords: Covid-19; Post Partum Mother; Stress Pendahuluan: Dari data Dinas Kesehatan Kota Bandar Lampung pada tahun 2020 tiga besar cakupan ibu post partum di Puskesmas Kota Bandar Lampung diantaranya adalah tertinggi di Puskesmas Panjang 14,29%, Puskesmas Kedaton 11,83%, Puskesmas Sukaraja 10,92%. Data pendahulu yang dilakukan di Puskesmas Kedaton dengan melihat jumlah ibu hamil pada bulan November berjumlah 54 ibu post partum, dan data pendahulu yang dilakukan di Puskesmas Sukaraja dengan melihat jumlah ibu hamil pada bulan November tahun 2021 sebanyak 80 ibu post partum Tujuan: Diketahui gambaran Covid-19 terhadap stres ibu post partum di Wilayah Kerja Puskesmas Kota Bandar Lampung Tahun 2022. Metode: Jenis penelitian kuantitatif, metode penelitian deskriptif, populasi dan sampel yaitu  ibu post partum di Puskesmas Sukaraja Dan Puskesmas Puskesmas Kedaton Kota Bandar Lampung, teknik sampling menggunakan purposive sampling. Analisa data menggunakan univariat dengan menyajikan persentase data Hasil: Jumlah ibu post partum di Puskesmas Sukaraja dan Puskesmas Kedaton sebanyak 50 responden (100%). Responden tidak terpapar Covid-19 partum di Puskesmas Sukaraja dan Puskesmas Kedaton sebanyak 50 responden (100%). Gambaran stress ibu post partum di Puskesmas Sukaraja dengan kategori normal 5 responden (10,0%), stress ringan 11 responden (22,0%), stress sedang 22 responden (44,0%), dan stress berat sebesar 12 responden (24,0%). Sedangkan di Puskesmas Kedaton dengan kategori  normal 11 responden (22,0%), stress ringan 14 responden (28,0%), stress sedang 15 responden (30,0%), dan stress berat sebesar 10 responden (20,0%). Simpulan: Gambaran stres ibu post partum di Puskesmas Sukarja dan Kedaton sama-sama pada tingkat stress sedang, dengan persentase 44% untuk Puskesmas Sukarja dan 30% untuk Puskesmas Kedaton. Saran: Bagi tenaga kesehatan diharapkan lebih meningkatkan upaya penyuluhan yang baik kepada individu dan keluarga, khusunya ibu hamil dan post partum.